THE INFLUENCE OF WORK ENVIRONMENT AND WORK DISCIPLINE ON WORK PRODUCTIVITY WITH WORK MOTIVATION AS A VARIABLE MODERATOR - Nina Yuliana; Suhardi M Anwar; Ilham Tahier; Hadi Pajarianto (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study aims to evaluate the influence of work environment and work discipline on employee work productivity, as well as to examine the role of work motivation as a moderation variable in the relationship. The research method used was a quantitative survey, with data collected through a questionnaire from 100 employees using the snowball sampling technique. Data analysis was carried out using multiple linear regression analysis and Moderated Regression Analysis (MRA) with the help of SmartPLS 3.3 software. The results showed that the work environment had a significant influence on work productivity, while work discipline did not show a significant influence, Work Motivation had a significant effect on work productivity. In addition, work motivation is proven not to moderate the influence between the work environment and work discipline on work productivity. These findings emphasize the importance of a conducive work environment in increasing employee productivity.